Effects of dimension reduction of hyperspectral images in skin gross pathology. Issue 2 (1st February 2023) - Aloupogianni, Eleni; Ishikawa, Masahiro; Ichimura, Takaya; Hamada, Mei; Murakami, Takuo; Sasaki, Atsushi; Nakamura, Koichiro; Kobayashi, Naoki; Obi, Takashi
Abstract: Background: Hyperspectral imaging (HSI) is an emerging modality for the gross pathology of the skin. Spectral signatures of HSI could discriminate malignant from benign tissue. Because of inherent redundancies in HSI and in order to facilitate the use of deep‐learning models, dimension reduction is a common preprocessing step. The effects of dimension reduction choice, training scope, and number of retained dimensions have not been evaluated on skin HSI for segmentation tasks. Materials and methods: An in‐house dataset of HSI signatures from pigmented skin lesions was prepared and labeled with histology. Eleven different dimension reduction methods were used as preprocessing for tumor margin detection with support vector machines. Cluster‐wise principal component analysis (ClusterPCA), a new variant of PCA, was proposed. The scope of application for dimension reduction was also investigated. Results: The components produced by ClusterPCA show good agreement with the expected optical properties of skin chromophores. Random forest importance performed best during classification. However, all methods suffered from low sensitivity and generalization. Conclusion: Investigation of more complex reduction and segmentation schemes with emphasis on the nature of HSI and optical properties of the skin is necessary. Insights on dimension reduction for skin tissue could facilitate the development of HSI‐based systems for cancer margin detection at gross level.